Enterprise Risk Management Models - Olson, David L.; Wu, Desheng Dash (Springer, 2017)
Enterprise risk management has always been important. However, the events of the twenty-first century have made it even more critical. Nature has caused massive disruption, such as the tsunami that hit Fukushima in March 2011. Terrorism has seemed to be on the rise, with attacks occurring in the USA, Europe, and Russia with greater regularity, not to mention the even more common occurrences in the Middle East. Human activities meant to provide benefits such as food modification and medicine have led to unintended consequences. The generation of energy involves highly politicized trade-offs between efficient electricity and carbon emissions, with the macro-level risk of planetary survival at stake. Oil transport has experienced traumatic events to include the BP oil spill in 2010. Risks can arise in many facets of business. Businesses in fact exist to cope with risk in their area of specialization. But chief executive officers are responsible to deal with any risk fate throws at their organization. The first edition of this book was published in 2010, reviewing models used in management of risk in nonfinancial disciplines. It focused more on application areas, to include management of supply chains, information systems, and projects. It included review of three basic types of models: multiple criteria analysis, probabilistic analysis, and business scorecards to monitor risk performance. This second edition focuses more on models, with the underlying assumption that they can be applied to some degree to risk management in any context.We have updated case examples and added data mining support tools. When we return to look at risk management contexts, we demonstrate use of models in these contexts. We have